2.9 Catalytic Reduction of Nitriles - Bagal,D. B.; Bhanage,B. M. (Catalytic Reduction in Organic Synthesis 2, 2018)
Catalytic reduction of nitriles is an important industrial process for the one-step synthesis of diverse amines. Despite this, the selective reduction of nitriles to the corresponding amines has so far been less investigated compared to the reductions of C=C, C=O, C=N, and NO2 units. This is primarily due to high redox potential of nitriles compared to other carboxylic acid derivatives, low C–CN bond dissociation energy, the various factors that control the selectivity, low selectivity toward primary amines, and significant amounts of secondary amine formation. In recent years, great success has been achieved in the chemoselective reduction of nitriles using homogeneous transition-metal catalysts, but a major limitation of such catalysts is often their poor stability. Alternatively, heterogeneous catalytic systems represent an economic and simple alternative for these transformations. However, the use of heterogeneous catalysts for the selective reduction of nitriles to primary amines has been not well explored to date.
Keywords: Referencework; nitriles; amines; hydrogenation; homogenous catalysis; heterogeneous catalysis; reduction